Project on Human Development in Chicago Neighborhoods (PHDCN): Home and Life Interview, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One of the measures composing the Longitudinal Cohort Study was the Home and Life Interview. The Home and Life Interview was a restructured interview based on the Home Observation for Measurement of the Environment (HOME) inventory used in Wave 1. The Home and Life Interview, like the HOME inventory, sought to observe the developmental environment in which children belonging to the Longitudinal Cohort Study sample were raised. The Home and Life Interview was designed to capture the absence or presence of certain cognitive stimuli, including varied learning experiences and diverse educational materials. The Home and Life Interview also measured the extent and nature of the interactions that occurred between the subject and his or her primary caregiver. In contrast to Wave 1, particular emphasis was placed on evaluating the relationship between the subject and the subject's father or, in the father's absence, a male father figure. An important feature of the Wave 1 HOME inventory was the data collected that described the interior and exterior conditions of the respondent's home and neighborhood. Similar observations were recorded, however, for Wave 2. This information was documented in the Interviewer Impressions data found in PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): INTERVIEWER IMPRESSIONS (PRIMARY CAREGIVER), WAVE 1, 1997-2000 (ICPSR 13631) and in PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): INTERVIEWER IMPRESSIONS (SUBJECT), WAVE 1, 1997-2000 (ICPSR 13632).